The role of internal auditing in improving the quality of accounting information: The General Authority for Endowments and Islamic Affairs in Tripoli (International Journal of Financial, Administrative and Economic Sciences, 2026)
This research aims to identify the role of internal auditing in improving the quality of accounting information at the General Authority for Endowments and Islamic Affairs in Tripoli. This is achieved by analyzing the relationship between the effectiveness, independence, and impartiality of internal auditing, on the one hand, and the quality of accounting information, on the other. To achieve the research objectives, the descriptive-analytical approach was adopted, as it is best suited to the nature of the research topic. This approach allows for the description and analysis of the phenomenon under investigation using appropriate statistical methods. The primary data for the research was collected through a questionnaire designed for this purpose. This questionnaire was distributed to a purposive sample of employees directly involved in accounting and oversight processes within the Authority. Thirty-two (32) questionnaires were distributed, and twenty-eight (28) were returned and deemed valid for statistical analysis.The results of the descriptive analysis showed high arithmetic means for the questionnaire's axes, indicating a high level of agreement among the sample regarding the effectiveness of internal auditing, the independence of the internal audit department, and the quality of accounting information within the Authority under study. The reliability test results using Cronbach's alpha coefficient demonstrated a high degree of internal consistency in the research instrument, reflecting its reliability and suitability for statistical analysis. Normality tests also confirmed the data's suitability for parametric statistical methods. Furthermore, correlation analysis revealed a strong, statistically significant, positive relationship between the effectiveness and independence of internal auditing and the quality of accounting information, thus supporting the main research hypothesis. Based on these findings, the research concluded with several recommendations, most notably the need to strengthen the independence of the internal audit department, enhance the competence of internal auditors, update internal audit procedures and methods, and maximize the use of audit findings to improve the quality of financial reports within the organization.
Keywords: Internal Auditing; Quality of Accounting Information; General Authority for Endowments and Islamic Affairs; Tripoli